Therapeutic implications of a combined diagnostic workup including endomyocardial biopsy in an all‐comer population of patients with heart failure: a retrospective analysis. (10th May 2018) - Sotiriou, Efthymios; Heiner, Susanne; Jansen, Thomas; Brandt, Moritz; Schmidt, Kai Helge; Kreitner, Karl‐Friedrich; Emrich, Tilman; Schultheiss, Heinz‐Peter; Schulz, Eberhard; Münzel, Thomas; Wenzel, Philip
Abstract: Background: Aetiology of heart failure (HF) often remains obscure. We therefore evaluated the usefulness of a combined diagnostic approach including cardiac magnetic resonance imaging (CMRI) and endomyocardial biopsy (EMB) to assess the cause of unexplained cardiomyopathy underlying HF. Methods and results: We retrospectively investigated 100 consecutive patients (36% women, mean age 53.6 ± 18.8 years) presenting with unexplained cardiomyopathy (HF with reduced ejection fraction or left ventricular hypertrophy; excluding ischaemic and valvular heart disease; left ventricular ejection fraction 31.6 ± 13.9%, Left ventricular end‐diastolic pressure 18.2 ± 9.3 mmHg, heart rate 89 ± 26.6 b.p.m.; mean ± SEM) at the University Medical Center Mainz. We performed electrocardiography, echocardiography, CMRI, and cardiac catheterization with EMB analysed at a Food and Drug Administration‐approved reference centre in 100%, 94%, 69%, and 100% of patients, respectively. On the basis of CMRI findings, electrocardiography, echocardiography, and medical history, the exact cause of cardiomyopathy remained uncertain in 37 of 69 cases (53.6%). In EMB, 25% of patients had viral replication, 23% had inflammation defined as lymphocytic infiltrations without active virus replication, 1% had giant cell myocarditis, and 1% had eosinophilic myocarditis. After diagnostic workup including EMB findings, the cause of cardiomyopathy remained unidentified in 14% of the cases, classified as idiopathic dilated cardiomyopathy or hypertrophic cardiomyopathy in 10% or 4%, respectively. EMB helped to discuss a causal treatment strategy of HF involving immunosuppression or antiviral treatment in 53% of patients, which was opted for in 12% of the patients. Conclusions: A comprehensive workup including imaging and EMB in an all‐comer population of patients with HF may help physicians to improve diagnostics of unexplained cardiomyopathy in the majority of cases.